Artificial Intelligence in Politics: Opportunities and Challenges for Digital Democracy - Pirdaus, Dede Irman; Surya, Dhika (Communication in Research and Publications (CRP), 2025)
The development of artificial intelligence (AI) in the last two decades has significantly changed the face of democratic politics. AI is used in political campaigns, policy-making, and interactions between governments and citizens. For example, the launch of an AI tool called Nostrada in the UK that allows the public to interact with digital avatars of members of parliament, and the use of AI in the 2024 US election campaign to personalize messages and raise funds. However, the use of AI also poses major risks, such as the spread of disinformation through deepfakes and social media bots, and the amplification of algorithmic bias that can harm certain groups. AI systems that operate as “black boxes” pose challenges to transparency and accountability in political decision-making, thereby reducing public trust. Several countries, especially the European Union, have begun to implement regulations to prevent the misuse of AI, such as transparency obligations and deepfake detection. In addition to regulations, digital literacy is key to strengthening critical public participation in digital content. This study uses a qualitative-descriptive approach with a literature review to analyze the benefits and risks of AI in politics. The results emphasize the need for cross-sector collaboration to develop ethical and transparent policies so that AI strengthens digital democracy, not weakens it. This study highlights the importance of balancing technological innovation and protecting democratic values ​​in the face of an increasingly complex digital era.